The Presumption of Labor in the New Labor Procedure Law - Fajardo Mori, Martín (2016)
This article focuses on the analysis and use of the institutions that are used in the new work process in order to give effective protection to workers in a process who were imposes a minimum duty of proof, and in turn, serve to combat fraud in hiring.